2016
DOI: 10.1186/s40644-016-0096-y
|View full text |Cite
|
Sign up to set email alerts
|

Impact of combined FDG-PET/CT and MRI on the detection of local recurrence and nodal metastases in thyroid cancer

Abstract: BackgroundSuspected recurrence of thyroid carcinoma is a diagnostic challenge when findings of both a radio iodine whole body scan and ultrasound are negative. PET/CT and MRI have shown to be feasible for detection of recurrent disease. However, the added value of a consensus reading by the radiologist and the nuclear medicine physician, which has been deemed to be helpful in clinical routines, has not been investigated. This study aimed to investigate the impact of combined FDG-PET/ldCT and MRI on detection o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 37 publications
1
32
2
Order By: Relevance
“…Previous studies in patients with NPC and other head and neck cancers have indicated that 18 F-FDG PET/CT was superior to CT and MRI for metastasis detection in CLNs 23 - 25 . However, the superiority of 18 F-FDG PET/CT for MRI-negative lymph nodes has not been demonstrated clearly.…”
Section: Discussionmentioning
confidence: 96%
“…Previous studies in patients with NPC and other head and neck cancers have indicated that 18 F-FDG PET/CT was superior to CT and MRI for metastasis detection in CLNs 23 - 25 . However, the superiority of 18 F-FDG PET/CT for MRI-negative lymph nodes has not been demonstrated clearly.…”
Section: Discussionmentioning
confidence: 96%
“…However, this reflects the situation in routine clinical imaging of well-differentiated NETs, where—because of the slow growth of these tumors and the rather favorable prognosis in terms of survival—follow-up examinations are more common than pretherapeutic staging. Another limitation that our study shares with previous studies of similar design 24 , 28 , 29 is our use of a composite standard of reference for lesion verification, which was mostly based on previous imaging and follow-up examinations. While biopsies would have been the most reliable and thus preferable means of solving discrepancies between PET/MRI and PET/CT, this would not have been clinically feasible and would even have been unethical, as it would not have affected the management of any of these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, radiation exposure is not an issue with MRI. However, similar to CT, MRI is not recommended in the routine clinical workup of all thyroid cancer patients of a younger age [56].…”
Section: Ct and Mrimentioning
confidence: 99%